Design unit to treatment feed water for power stations - علي, علي; شاش, ميساء; شاهين, هيثم; زيدان, بشار (Latakia University Journal -Engineering Sciences Series, 2020)
In this research simple unite has been manufactured to recycle wastewater using available materials like sand and coal filter, UV lamp, and electrochemical cell. simple unite reduced Turbidity and reduced hardness 91.2% and 98% respectively. The purified sample verified standard specifications of boiler water of power stations in respect of Hardness, turbidity and conductivity. The electrochemical cell in The simple unit played important role in improving efficiency of water treatment, this is due to its ability to produce hydroxyl ions, which can reducedpositive ions like calcium and magnesiumand iron ions, the coal and sand played slight role in decreasing hardness value of water, this is related to adsorbent feature of them, Bacterial analysis revealed that ultra violet (UV) killed Bacterial colony in the water sample.